Greater Maternal Dietary Fiber Intake Protects Against Infant Central Fat Accretion Related to High Maternal Fructose Intake. (7th June 2021) - Hull, Holly; Herman, Amy; Hand, Lauren; Carlson, Susan
Abstract: Objectives: Greater maternal fructose intake is linked to greater offspring fat accrual, while dietary fiber intake is related to lower weight gain and a more favorable adipose tissue distribution. However, data are lacking investigating these relationships in the especially critical time of pregnancy and early infancy. We explored the relationships between maternal fructose and fiber intake on early offspring adipose tissue accrual. Methods: This is a secondary analysis using data from a prenatal DHA supplementation trial (ADORE HD083292). At enrollment (12–16 wks), women completed the DHQ II food frequency questionnaire. ADORE mothers were invited to enroll in the GAINS infant follow up study (DK118220). Infant skinfolds were assessed two weeks and six months at three central sites (suprailiac, subscapular, flank) and three peripheral sites (biceps, triceps, thigh). Median splits were calculated for maternal fructose and total dietary fiber intake (< 50 th percentile, ≥50 th percentile). An ANCOVA assessed the main effects of maternal fructose and fiber intake on infant fat accrual (central and peripheral). Results: Data were available on n = 61 infants. For the change in infant central FM, a significant interaction (p = 0.034) was found between maternal fructose intake and dietary fiber intake. No effect of fiber was found in offspring exposed to low fructose intake. However, in offspring exposed to high fructose intake during pregnancy, exposure to high maternal dietary fiber intake was related to lower central FM accrual (high fiber intake: 4.2 mm vs. low fiber intake 6.9 mm; p = 0.016). No significant main effects or interaction was detected for the change in peripheral FM. Conclusions: In offspring exposed to greater maternal fructose consumption during pregnancy, greater maternal intake of dietary fiber was related to lower early offspring central fat accretion. Interventions targeting to decrease maternal fructose consumption and increase maternal dietary fiber intake may positively impact offspring fat accretion. Funding Sources: NIH Awards R01 HD083292 and R01 DK118220.